The Bioanthropology of the Early Iron Age Site of Prohear (Cambodia) - Krais, Simone; Reinecke, Andreas; Sonetra, Seng; Laychour, Vin (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The Early Iron Age site of Prohear in southeastern Cambodia was discovered and nearly completely looted in 2007. From 2008 to 2011, the German Archaeological Institute together with the Memot Centre for Archaeology carried out rescue excavation of 76 intact or only partly looted graves directly under the main road through the village. Of these, 42 burials still contained human remains. This study presents the fi nal results of the bioanthropological analyses and their regional and chronological context. Given the fact that human bones were poorly preserved in the majority of the burials, most of our information – such as the age at death distribution, health and disease, nutrition or on migration and integration – has come from the teeth.